The Relationship between Gestational Age, Birth Weight, and Mode of Delivery with the Incidence of Neonatal Jaundice at Bunda Hospital, Palembang City in 2026 - Risky Amey Yolanda; Rini Gustina Sari; Arie Anggraini (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Neonatal jaundice is a common condition characterized by yellow discoloration of the skin, mucous membranes, and sclera resulting from elevated blood bilirubin levels and may cause complications if not appropriately managed. This study examined the relationships between gestational age, birth weight, mode of delivery, and neonatal jaundice at Bunda Hospital, Palembang City, in 2026. A quantitative cross-sectional design was employed using medical-record data from 93 neonates. Data were analyzed using univariate statistics and bivariate Chi-square tests at a significance level of α = .05. Of the 93 neonates, 16 (17.2%) had neonatal jaundice, whereas 77 (82.8%) did not. Twenty-two neonates (23.7%) were born preterm, and 71 (76.3%) were born at term. Similarly, 22 neonates (23.7%) had low birth weight, while 71 (76.3%) had normal birth weight. Regarding mode of delivery, 37 neonates (39.8%) were recorded as having normal deliveries, and 56 (60.2%) were delivered by cesarean section. Bivariate analysis demonstrated significant associations between neonatal jaundice and gestational age (p < .001; OR = 32.741), birth weight (p < .001; OR = 60.375), and mode of delivery (p = .014; OR = 0.171). These findings indicate that gestational age, birth weight, and mode of delivery are significantly associated with neonatal jaundice among neonates treated at Bunda Hospital. The findings may support the early identification and closer clinical monitoring of neonates with characteristics associated with jaundice.